Final outcome of a second trimester low-positioned placenta: A systematic review and meta-analysis. (September 2019) - Jansen, Charlotte H.J.R.; Kleinrouweler, C. Emily; van Leeuwen, Liesbeth; Ruiter, Laura; Limpens, Jacqueline; van Wely, Madelon; Mol, Ben W.; Pajkrt, Eva
Abstract: Low-positioned placentas which are located in the lower uterine segment (LUS), either a low-lying placenta or a placenta previa, are associated with increased obstetric risks. However, most second trimester low-positioned placentas resolve during pregnancy and have a higher position in the third trimester, without posing any risks. We performed a systematic review and meta-analysis to evaluate the proportion of second trimester low-positioned placentas that have a position towards the fundus in the third trimester. Our aim was to find a cut-off value that included all women in whom the placenta will remain low in the third trimester, thus who are at increased risk of obstetric complications. Subsequently, we assessed whether an anterior or posterior placental location influenced this proportion. We searched MEDLINE and EMBASE and clinicaltrials.gov up to April 2019 for studies on the sonographic follow-up of second trimester low-positioned placentas, with a distance between the placenta and the internal os of the cervix of 20 mm or less at a gestational age of above 15 week and a follow up after 28 weeks. Studies were scored on methodological quality using the Newcastle-Ottowa Scale (NOS). A meta-analysis was conducted to summarize the proportion of second trimester low-positioned placentas with a position towards the fundus in the third trimester. We calculated the proportion at different cut-off values of the distance from the placental edge to the internal os of the cervix (0 mm, 10 mm and 20 mm). Also, anteriorly and posteriorly located placentas and women with and without a prior cesarean delivery were compared. We included 11 eligible studies which reported on 3586 women with a low-positioned placenta in the second trimester. Proportions of placentas with a position towards the fundus in the third trimester ranged between 0.63 and 1.0. Pooled proportions were 0.90 (95% CI 0.87-0.93) for IOD <10 mm and 0.80 (95% CI 0.74-0.85) for IOD < 0 mm. Due to heterogeneity between studies, the subgroup of <20 mm could not be pooled. Overall, anteriorly located placentas more often had a position towards the fundus in the third trimester, but studies did report conflicting results. Prior cesarean section had no influence except for an IOD of <0 mm, in which women without a prior cesarean delivery more often had a placenta towards the fundus. The majority of second trimester low-positioned placentas will be located towards the fundus at the time of follow-up. However, we could not determine a cut-off value for anterior and posterior placentas that included all women at high risk. The cut-off value, placental side and prior cesarean section should be assessed in a large prospective observational study.